Peran Kepala Desa Dalam Pengembangan Pariwisata di Desa Luan Kecamatan Muara Samu Kabupaten Paser - Ahmad Al Arafi; Muh. Jamal; Iman Surya (Jurnal Ilmu Pemerintahan, 2022)
This study aims to identify and describe the role of the village head in tourism development in Luan Village, Muara Samu District, Paser District. This study uses three indicators of the role of the village head, namely motivator, facilitator and mobilizer and aims to determine the supporting factors that inhibit funding in tourism development in Luan Village. This type of research is descriptive qualitative. The source of data collection was done by interviewing key informants and informants. The key informant is the village head of Luan. While the informants are village officials, the community, tourism awareness groups and tourists. Data analysis was carried out by collecting data, condensing data, presenting data and drawing conclusions. The results of this study indicate that the role of the village head in tourism development has gone very well, where the village head as a motivator always provides motivation, enthusiasm and input to village officials and village communities. The village head also acts as a facilitator by being a good resource person for a problem in facilitating community needs by providing tools and materials for making facilities. In addition, the village head also acts as a mobilizer by mobilizing village and community officials to carry out development activities. Supporting factors in tourism development are that the community knows there is tourism potential that can be developed, the role of the village government and the community to support development and easy coordination with related parties. The inhibiting factors in tourism development are the status of land ownership, lack of public awareness to maintain and preserve tourism and the lack of facilities and infrastructure.